Analisis Pemanfaatan Sampah Kulit Manggis di Desa Pangradin Kecamatan Jasinga Kabupaten Bogor - Jamaludin , Jamaludin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The residents of Pangradin Village in the Jasinga District of Bogor Regency have minimal knowledge about the benefits of mangosteen peel. Usually, mangosteen peel is just considered organic waste, even though it actually has many other benefits. The community service in Pangradin Village is carried out through approaches such as counseling, Q&A, and discussions. As a result, the community's understanding of the benefits of mangosteen peel for health can increase.